The change of coordinate system versus the area of parcels - Novikova, Elena; Yeropunova, Iryna; Palamar, Alena (Geodesy and Cartography, 2020)
The transition from one coordinate system to another creates many problems, one of which is the change in the area of land parcels. There are at least three reasons causing a change in the area of the parcels after transition from one coordinate system to another. 1. The change in area associated with the transition from one reference ellipsoid to another; 2. The change in area due to deformations caused by random and systematic errors of one of the coordinate systems; 3. The change in the area of the parcel associated with the properties of the projection of Gauss-Krüger. It is shown that the greatest change in the area of the parcel during the transition from CS-63 to UCS-2000 (the coordinate systems of Ukraine) is associated with the properties of the Gauss-Krüger projection. For the parcel of 1 hectare, extreme changes in the area at the borders between the zones of the coordinate systems, can reach the size of 1.95 sq. m. When using local coordinate systems based on UCS-2000, extreme area changes can reach 7.02 sq. m per 1 hectare. It is concluded that the difference in the areas of parcels caused by the properties of the Gauss-Krüger projection could have been avoided if the prime meridians of the zones in the UCS-2000 and CS-63 systems coincided.